“Vi insegno come invecchiare bene”. Diseguaglianze generazionali nella società dei consumi di massa, dal secondo dopoguerra agli anni Novanta - Pizzirani, Silvia (Disuguaglianza e generazioni in Italia 1914-2008, 2026)
This article aims to reconstruct public perception, stereotypes and possible transformations of the image of the elderly, between the second post-war period and the 1990s. An attempt has been made to bring together economic, scientific, and cultural aspects, with particular attention to the world of advertising, which has only recently begun to show interest in the elderly, due to a cultural stereotype that considered old age to be a problematic phase, marked by a departure from the active and productive world. Two widely circulated magazines (La Domenica del Corriere and Oggi), television programmes, scientific literature and advertising, both in magazines and on television, were analysed.